Accusing Heresy is a Heresy: How Heresy Became an Instrument in Political Sectarianism - Dina Yulianti; Otong Sulaeman; Muhammad Ilyas (Religio: Jurnal Studi Agama-agama, 2020)
The Islamic world in recent years, along with the phenomenon of the Arab Spring, witnesses the strengthening of sectarianism and takfirism which has even sparked the war in parts of the region. One of the main concepts used by the takfiris was puritanism, namely the obligation to dispose of other groups who are considered to have carried out heresy. This first, the determination of heresy article argues three main theses, by the takfiris is actually a heresy. The second thesis, heresy is not merely theological discourse but an instrument in the politics of sectarianism. The third one, heresy indictment is a postcolonial tool to weaken the Islamic World. This article uses the concept of politics of sectarianism, postcolonialism, and siyasi ijtima'i interpretation of Qur’an verses with maudhu’i method.